Ethnic Minority Human Resourcs in Psychology Directory - Olmedo, Esteban L., Comp.; American Psychological Association, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
Minority members of the American Psychological Association (APA) who have expressed a desire to serve as professional resources are listed in this directory. Individuals are identified under one of four broad categories of ethnic minority groups: American Indian/Alaska Native, Asian/Pacific American, Black/Afro American, and Hispanic. Within each category entries are listed alphabetically. For each entry name, address, telephone number, ethnic self-identification, areas of professional expertise, and APA division membership are given. (CMG)
Availability: Ethnic Minority Afairs Office, American Psychological Association, 1200 17th Street, N.W., Washington, D.C. 20036 (no charge for single copies; requests should be accompanied by self-addressed mailing label).
ERIC Note: Compiled and edited at the request of the Board of Ethnic Minority Affairs by the Office of Ethnic Minority Affairs.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Alaska Natives; American Indians; Asian Americans; Blacks; Ethnic Groups; Hispanic Americans; Human Resources; Minority Groups; Pacific Americans; Psychologists; Reference Materials, Directories/Catalogs.